2005
DOI: 10.1016/j.oraloncology.2005.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of invasion and metastasis in oral cancer by targeting urokinase-type plasminogen activator receptor

Abstract: There have been reports of strong correlations between poor prognosis in various cancers and concomitant expression of urokinase-type plasminogen activator (uPA) and its surface receptor (uPAR). We and others have previously shown that the uPA system plays a significant role in a subset of head and neck squamous cell carcinoma. In the present study, we found that uPAR is required for invasion and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Seven of the nine showed significant inhibition by a pooled t test. Among these nine completely blocked genes were arachidonate 5-lipoxygenaseactivating protein (Alox5ap), urokinase plasminogen activator (Plaur) and osteopontin (Spp1/Opn), already shown to be involved in driving tumor promotion and progression (29)(30)(31)(32). Despite the P value of 0.062, the inhibition of TPA-induced Opn mRNA expression by TAM67 was confirmed by quantitative PCR (Table 1), showing about 15-fold inhibition.…”
Section: Resultsmentioning
confidence: 96%
“…Seven of the nine showed significant inhibition by a pooled t test. Among these nine completely blocked genes were arachidonate 5-lipoxygenaseactivating protein (Alox5ap), urokinase plasminogen activator (Plaur) and osteopontin (Spp1/Opn), already shown to be involved in driving tumor promotion and progression (29)(30)(31)(32). Despite the P value of 0.062, the inhibition of TPA-induced Opn mRNA expression by TAM67 was confirmed by quantitative PCR (Table 1), showing about 15-fold inhibition.…”
Section: Resultsmentioning
confidence: 96%
“…It is involved in localizing and promoting cell-surface plasminogen activation, plasmin formation and localized degradation of the extracellular matrix. 42 Overexpression of UPAR has been found in many cancers 23,[43][44][45][46] including pancreatic cancer, and contributes to tumor invasion and metastasis. 24,25 Recent studies by Ellis and colleagues have shown that pancreatic metastatic disease is dependent upon the UPA/ UPAR system, and that system activation and subsequent metastases is (i) mediated by insulin growth factor-1, hepatocyte growth (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture was performed as described previously by Nozaki et al (12). Cell lines were derived from OSCC with the following grades of invasiveness, according to the Yamamoto-Kohama criteria (9): HSC-4 and OSC-20 cells of grade 3 described as mildly invasive; OSC-19 and OTC-04 of grade 4C described as highly invasive; HOC313 and TSU of grade 4D described as most highly invasive.…”
Section: Specimensmentioning
confidence: 99%